Building Capacity for Workplace Health Promotion: Findings From the Work@Health® Train-the-Trainer Program. Issue 6 (November 2017) - Lang, Jason; Cluff, Laurie; Rineer, Jennifer; Brown, Darigg; Jones-Jack, Nkenge
Small- and mid-sized employers are less likely to have expertise, capacity, or resources to implement workplace health promotion programs, compared with large employers. In response, the Centers for Disease Control and Prevention developed the Work@Health ® employer training program to determine the best way to deliver skill-based training to employers of all sizes. The core curriculum was designed to increase employers' knowledge of the design, implementation, and evaluation of workplace health strategies. The first arm of the program was direct employer training. In this article, we describe the results of the second arm—the program's train-the-trainer (T3) component, which was designed to prepare new certified trainers to provide core workplace health training to other employers. Of the 103 participants who began the T3 program, 87 fully completed it and delivered the Work@Health core training to 233 other employers. Key indicators of T3 participants' knowledge and attitudes significantly improved after training. The curriculum delivered through the T3 model has the potential to increase the health promotion capacity of employers across the nation, as well as organizations that work with employers, such as health departments and business coalitions.